2013
DOI: 10.1590/s0004-282x2013005000003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental settings and families' socioeconomic status influence mobility and the use of mobility devices by children with cerebral palsy

Abstract: Functional mobility of children with cerebral palsy (CP) is influenced by personal and environmental factors, serving as barriers and/or facilitators and impacting on children's strategies and functional outcome. OBJECTIVES: To describe typical mobility methods used by children with CP at home, school and community and to compare them across family's socioeconomic levels (SES). METHODS: The Functional Mobility Scale was used to assess mobility of 113 children with CP of high and low SES at home, school, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Two retrospective population‐based studies in the USA have explored the possible relationship between race and risk of CP and found that the risk of CP was higher among black children than white children; a similar association was found for risk of severe CP, as determined by the GMFCS level. A recent study in Brazil showed that SES influences functional mobility and the use of assistive mobility devices in children with CP …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two retrospective population‐based studies in the USA have explored the possible relationship between race and risk of CP and found that the risk of CP was higher among black children than white children; a similar association was found for risk of severe CP, as determined by the GMFCS level. A recent study in Brazil showed that SES influences functional mobility and the use of assistive mobility devices in children with CP …”
Section: Discussionmentioning
confidence: 99%
“…At an individual level, maternal SES is recognized as a robust predictor of child health . Studies to date suggest that children with CP, born to disadvantaged families, have more severe phenotypes as defined by spastic quadriparesis, poor mobility, and cognitive impairment . We hypothesize that, beyond individual‐level SES factors, socio‐economic indicators related to families' areas of residence may also affect CP outcomes, with areas associated with chronic exposure to socio‐economic stressors (e.g.…”
mentioning
confidence: 99%
“…Children with similar types of cerebral palsy (CP) living in places with facilitating disability services and structures have been found to have higher participation scores 7 . Furthermore, children with CP with the same motor function classification showed different patterns of mobility in different contexts 6 . Parents perceived factors such as lack of social support, negative attitudes, and inadequate physical environment as barriers to the participation of their children in school 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Rodby-Bousquet e Hagglund 15 destacam que quase um terço das crianças com paralisia cerebral é dependente de equipamentos para a locomoção. Cury, Figueiredo e Mancini 16 explicitam que crianças e adolescentes com paralisia cerebral rotineiramente precisam de equipamento de assistência e treino para mobilidade funcional, definido de acordo com as habilidades do usuário e com o ambiente em que a mobilidade irá ser desempenhada. Uma cadeira de rodas pode prover deslocamento, permitindo envolvimento em tarefas desejadas e/ou necessárias ao longo de um dia, ampliando a oportunidade de envolvimento em atividades e na participação.…”
Section: Discussionunclassified